Medieval Holy Women and the Desire for Death - Barr, Jessica (Notre Dame Press, 2026)
o.a. Christina de Wonderbare, Elizabeth van Spalbeek, Beatrijs van Nazareth

Mémoires enchâssées. Saint Landoald, le diocèse de Liège et l’abbaye Saint‑Bavon de Gand à la fin du x e siècle - Mériaux, Charles (Mémoire et communautés dans les sociétés du haut Moyen Âge (VIe-XIIe siècle), 2026)

Mournful Travelers Gazing at the Chartreuse: Carthusian Representation and Self-Representation from the Late Middle Ages to Modern Times - Gaens, Tom (Carthusian Monasticism. History, Life, World, Texts, 2026)

Mapping Medieval Marriage: Canon Law, Regionalism, and the Evolution of Legal History - Delameillieure, Chanelle (Journal of Medieval History, 2025)

Modélisation et caractérisation de l’environnement des sites d’implantation des abbayes - Ollive, Vincent; Champougny, Anaïs; Charignon, Agnès (Implantation et évolution des monastères cisterciens entre Seine et Rhin. 12e-18e siècle, 2025)

Modelling the Middle Dutch Prayer Book (c. 1380–1550). The PRAYER Data Model for Manuscripts and Early Printed Books - Dlabačová, Anna; Van Eldere, Irene (Quaerendo, 2025)

Moeilijke jaren voor Vlierbeek (1456-1642) - Janssens, Gustaaf (Een plek die Vlierbeek heet. 900 jaar geschiedenis van een Leuvense abdij. 1125-2025, 2025)

Monastères: une base de données collaborative sur les établissements réguliers de la France médiévale - Deflou-Leca, Noëlle; Crouzevialle, Rémi (Implantation et évolution des monastères cisterciens entre Seine et Rhin. 12e-18e siècle, 2025)

The Mystical Union Between Christ and His Brides. Devotional Prints as a Source for Catholic Women’s History - Verheggen, Evelyne (Early Modern Low Countries, 2025)

Magistrae of the Beguines of Valenciennes and Their Social Networks - Lu, Huanan (Journal of Medieval History, 2024)

Manna and the Mystery of Non-Death in the Late Medieval Liturgy of St. John the Evangelist: From Ephesus to ’S-Hertogenbosch - Saucier, Catherine (Viator, 2024)

Mannen gestraft voor hekserij in de Vlaams Westhoek (1570-1620) - Monballyu, Jos (Westhoek, 2024)

The Medieval Clergy, 800-1250. A Sourcebook - Ott, John S.; Trumbore Jones, Anna (Mediaeval Sources in Translation, 2024)
Keywords: Vertaling

Meditation and Imagination in Geert Grote's De quattuor generibus meditabilium - Falque, Ingrid (Ons Geestelijk Erf, 2024)

Meester Wulfaert Boussemaere (°ca 1485-Sint-Jan, 1522) chirurgijn in Hoge Zieken - Boussemare, Noël (Westhoek, 2024)

Merit and Justification in Le baston de la foy of Guy de Brès (Chapter 6) - Lane, Anthony N.S. (Church History and Religious Culture, 2024)

Middeleeuwse vrouwen in het boekenbedrijf. Graduale van de Magdalenaleprozerie. 1504 - Hauwaerts, Evelien (Een geschiedenis van België in 100 voorwerpen. Van de prehistorie tot nu, 2024)

The Middle Dutch Sermon. A Premature Synthesis - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Miracles and Misadventures: Childhood and Public Health in the Late Medieval Low Countries - Coomans, Janna; Marschall, Bente (Journal of Medieval History, 2024)

The Monastery as a Literary Institution in the Low Countries (13th–16th Century) - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Monastic Women and Secular Economy in Later Medieval Europe, ca. 1200 to 1500 - Müller, Annalena (Routledge, 2024)

Monks, Monasteries, and Pastoral Care in the Carolingian Age: Some Remarks on Its Conditions - Kikuchi, Shigeto (Pastoral Care and Monasticism in Latin Christianity and Japanese Buddhism (ca. 800-1650), 2024)

The Mystic as Symbol. Ecstasy as Liturgical Participation in the Vita of Beatrice of Nazareth - Slaubaugh, Samantha (Medieval Mystical Women in the West. Growing in the Height of Love, 2024)

Mystical Culture and Literature in the Late Middle Ages - Mertens, Thom (Spiritual Literature in the Late Medieval Low Countries. Essays by Thom Mertens, 2024)

Mystical Hagiography in the Thirteenth Century: The Low Countries and Italy - Bartolomei Romagnoli, Alessandra (Medieval Mystical Women in the West. Growing in the Height of Love, 2024)

Mysticism by the Numbers: Beatrice of Nazareth’s Seven Manners of Love and Ida of Nivelles' ‘Eight Topics of Contemplation’ - Shahan, Lydia (Medieval Mystical Women in the West. Growing in the Height of Love, 2024)

Materiality and Archaeology of Women Religious - Collins, Tracy (Medieval women religious c. 800-c. 1500. New Perspectives, 2023)

On the meaning of gargoyles - Hartog, Elizabeth den (L’espace sacré au sein de l’église médiévale. Actes du colloque des 5 et 6 juin 2018, Université Paris Nanterre, MAE, 2023)

A Medical Anthology Customised ‘for the Consolation of the Sick’ in a Brussels Convent - Leerdam, Andrea van (Customised Books in Early Modern Europe and the Americas, 1400-1700, 2023)

Meditating the Unbearable in a Fifteenth-Century Netherlandish Manuscript Prayerbook with Printed Images - Melion, Walter S. (Vernacular Books and Their Readers in the Early Age of Print (c. 1450–1600), 2023)
Betreft Groenendaal Open access: https://brill.com/edcollbook-oa/title/63067
Keywords: Tekstuitgave

The Merovingians in Historiographical Tradition: From the Sixth to the Sixteenth Centuries - Fox, Yaniv (Cambridge University Press, 2023)

Mes meilleures heures de Nostre Dame. Les Heures de La Tramerie, un manuscrit vagabond - Vanwijnsberghe, Dominique (Scientia Artis, 2023)
Opdrachtgever van afgewerkt getijdenboek was Doornikse bisschop

Metaalslakken - Rijk, Patrice de (Sporen van Susteren. Archeologische vondsten uit een Karolingische abdij en een adellijk vrouwenstift. De basispublicatie, 2023)

Middeleeuws aardewerk voor circa 1000 AD - Koning, Jan de (Sporen van Susteren. Archeologische vondsten uit een Karolingische abdij en een adellijk vrouwenstift. De basispublicatie, 2023)

Middeleeuws koningschap Op zoek naar de wortels van de West-Europese monarchie - Leupen, Piet H.D. (Walburg Pers, 2023)

Ministry to the Sick and Dying in the Late Medieval Church - Izbicki, Thomas M. (The Catholic University Press, 2023)

Miracles de l’an mil - Barthélémy, Dominique (Mnémosya, 2023)

Mmmonk: Digital Innovation and Public Outreach with Medieval Monastic Manuscripts - Hauwaerts, Evelien (In Monte Artium, 2023)

Mmmonk verenigt de middeleeuwse manuscripten van vier Vlaamse abdijen - Hauwaerts, Evelien (Handelingen van het genootschap voor geschiedenis te Brugge, 2023)

Moderne tijden. Invloed van de Moderne Devotie in het Leuvense - Verweij, Michiel (Dieric Bouts. Beeldenmaker, 2023)

Monniken op de brandstapel - Dunk, Thomas H. von der (Historisch Nieuwsblad, 2023)

Ms. 237 de KU Leuven Libraries Special Collections. L’un des rares manuscrits du seizième siècle rédigé par un étudiant de l’université de Louvain - An Smets (De Gulden Passer, 2023)

Macht, bezit en samenleving rond het jaar 1000 - Doesburg, Jan van; Huiting, J.H. (De dam bij Wijk en het Kromme Rijngebied in de middeleeuwen, 2022)

Machtige ridders, burgerlijke herders. De Duitse Orde en haar priesters in het land van Maas en Rijn (1220-1800) - Mertens, Jozef (Bijdragen tot de geschiedenis van de Duitse Ordein de balije Biesen, 2022)

Magdalena’s gulden lethanien. A Late Medieval German-Dutch Meditation on the Passion - Rossano, Bram (Church History and Religious Culture, 2022)

Matérialité des limites, revendications foncières et jugements de Dieu. L’exemple du diocèse de Liège (IXe-XIIe siècles) - Maquet, Julien (Passions liégeoises. Mélanges en l’honneur de Bruno Demoulin, 2022)
Bestelnummer Rijksarchief 6330

Middeleeuwse mensen en hun verhalen - Künzel, Rudi (Verloren, 2022)

Missionarisches Mönchtum zwischen den Alpen und der Nordseeküste - Kleinjung, Christine (Handbuch der benediktinischen Ordensgeschichte. Band 1: Von den Anfängen bis ins 14. Jahrhundert, 2022)

Monachi peregrini. Irisch-slawische Sonderwege. Einflüsse aus der europäischen Peripherie. Die Schottenkloster - Flachenecker, Helmut (Handbuch der benediktinischen Ordensgeschichte. Band 1: Von den Anfängen bis ins 14. Jahrhundert, 2022)

The Monastic Reforms of 816-19: Ideals and Reality - Mériaux, Charles (Monastic Communities and Canonical Clergy in the Carolingian World (780-840). Categorizing the Church, 2022)

Monks Pray, Priests Teach, Canons Sing and the Laity Listens: The Regula Benedicti and Conceptual Diversity of Sacred Space in Carolingian Discourse - Czock, Miriam (Monastic Communities and Canonical Clergy in the Carolingian World (780-840). Categorizing the Church, 2022)

Mozes en zijn broer Aaron : een buitengewone cyclus 13de-eeuwse muurschilderingen ontdekt in de kapittelzaal van de Parkabdij - Bergmans, Anna; De Clercq, Lode; Lagaert, Joke (Monumenten en Landschappen, 2022)

Maguerite Porete et l’enquête de 1323 sur le béguinage Sainte-Élisabeth de Valenciennes - Lu, Huanan (Revue du Nord, 2021)

Manuscript production in the monastery of St Hieronymusdal in Lopsen, near Leiden - As-Vijvers, Anne Margreet W. (Oud Holland. Quarterly for Dutch Art History, 2021)

Maria, Onze Lieve Vrouw. Hemelkoningin en Redder in Alle Nood - Mulder-Bakker, Anneke B.; Beek, Lianne van (Geleefd geloof. Het geloofsleven van boeren en burgers in Friesland en de Ommelanden van Groningen, 1200-1580, 2021)

Marighen Dirckx, haar getijdenboek en het ‘verraad’ van Gouda - Abels, Paul H.A.M. (Tidinge van die Goude, 2021)

Marsilius von Padua und Francesco Petrarca in Lüttich - Haye, Thomas (Frühmittelalterliche Studien, 2021)

Medieval authorship and canonicity in the digital age. An introduction - Deploige, Jeroen; De Gussem, Jeroen (Interfaces. A Journal of Medieval European Literatures, 2021)

Medieval Authorship and Cultural Exchange in the Late Fifteenth Century. The Utrecht Chronicle of the Teutonic Order - Stapel, Rombert J. (The Military Religious Orders, 2021)

Medieval Badges. Their Wearers and Their Worlds - Rasmussen, Ann Marie (University of Pennsylvania Press, 2021)

The Medieval Booklists of the Southern Low Countries. Supplement: Additions and Corrections. Index of Manuscripts and Incunables. Index of Persons - Derolez, Albert; Victor, Benjamin; Bracke, Wouter (Peeters, 2021)

Mediteren over de oudste Mariëngaarder geschriften, 1163-1259 - Lambooij, Herman Th. M. (Macht, bezit en ruimte. Opstellen over de noordelijke Nederlanden in de middeleeuwen aangeboden aan Hans Mol bij zijn afscheid als bijzonder hoogleraar Geschiedenis van de Friese landen in de Middeleeuwen aan de Universiteit Leiden, 2021)

Memento muri. Stervenvermaningen als teken aan de wand - Boer, Dick E.H. de (Macht, bezit en ruimte. Opstellen over de noordelijke Nederlanden in de middeleeuwen aangeboden aan Hans Mol bij zijn afscheid als bijzonder hoogleraar Geschiedenis van de Friese landen in de Middeleeuwen aan de Universiteit Leiden, 2021)

Memoria rond Montfoort. Het testament van ridder Roelof de Rover van Montfoort - Weijert, Rolf de (Macht, bezit en ruimte. Opstellen over de noordelijke Nederlanden in de middeleeuwen aangeboden aan Hans Mol bij zijn afscheid als bijzonder hoogleraar Geschiedenis van de Friese landen in de Middeleeuwen aan de Universiteit Leiden, 2021)

Met eydel handen aanveert men geene winninghe. Landbouw, economie en landschap - Van Lani, Stefan (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)

Metamorfose van stad en devotie. Ontstaan en conjunctuur van kerkelijke, religieuze en charitatieve instellingen in Amsterdam in het licht van de stedelijke ontwikkeling, 1385-1435 - Melker, Bas R. de (Verloren, 2021)
Bewerkte versie van het proefschrift uit 2002 van Bas de Melker (1960-2018), voorzien van een epiloog met het nieuwe onderzoek

Middeleeuws Westerwolde - Noomen, Paul N. (Landschapsbiografie van Westerwolde, 2021)

Middeleeuwse bedevaartsplaatsen - Koldeweij, Jos (Geleefd geloof. Het geloofsleven van boeren en burgers in Friesland en de Ommelanden van Groningen, 1200-1580, 2021)

Middeleeuwse broekland- en veenontginningen langs Sethe en Reest - Wever, Bart; Spek, Theo (Macht, bezit en ruimte. Opstellen over de noordelijke Nederlanden in de middeleeuwen aangeboden aan Hans Mol bij zijn afscheid als bijzonder hoogleraar Geschiedenis van de Friese landen in de Middeleeuwen aan de Universiteit Leiden, 2021)

Middeleeuwse en latere constructies op de abdijhoeve Ten Bogaerde te Koksijde (W.-Vl.) - Lehouck, Alexander; Bakx, Ron (Archaeologia mediaevalis, 2021)

Middeleeuwse prefab en recycling voor de Dom - Vries, Dirk J. de (Bericht van de Stichting Vrienden van de Domkerk, 2021)

Military Orders and their Members as Elites - Sarnowsky, Jürgen (Virtuosos of Faith. Monks, Nuns, Canons, and Friars as Elites of Medieval Cultur, 2021)

The Mobilization of Thought. A Narratological Approach to Representations of Dream and Vision in Late Medieval Miracle Collections in the Low Countries - Van Mulder, Jonas (A Companion to Medieval Miracle Collections, 2021)

Moderne Devotie. Leven in kuisheid en armoede - Laven, Annemarie (Historisch Nieuwsblad, 2021)

Monastic Elites and Narratives of Distinction in the High Middle Ages - Vanderputten, Steven (Virtuosos of Faith. Monks, Nuns, Canons, and Friars as Elites of Medieval Cultur, 2021)

Monastic Elites Between the Struggle for Perfection and the Management of Economic Affairs - Röhrkasten, Jens (Virtuosos of Faith. Monks, Nuns, Canons, and Friars as Elites of Medieval Cultur, 2021)

Maiorem ecclesiam esse matrem omnium ecclesiarum totius villae: On the Sacral Topography of Nivelles based on the Liber ordinarius - Odenthal, Andreas (The Liber ordinarius of Nivelles (Houghton Library, MSLat 422). Liturgy as Interdisciplinary Intersection, 2020)

The mass in monastic practice: Nuns and Ordained Monks, c. 400-1200 - Griffiths, Fiona (The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

The matter of piety. Zoutleeuw’s church of Saint Leonard and religious material culture in the Low Countries (c. 1450-1620) - Suykerbuyk, Ruben (Studies in Netherlandish Art and Cultural History, 2020)

Mauvais mercredi et vendredi saint. Conflits politiques urbains et temps liturgique dans les Pays-Bas du Moyen Âge tardif - Dumolyn, Jan; Haemers, Jelle (Annales. Histoire, sciences sociales, 2020)

The medical role of monasteries in the Latin West, c. 1050-1300 - Brenner, Elma (The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

Medieval Monasticisms. Forms and Experiences of the Monastic Life in the Latin West - Vanderputten, Steven (Oldenbourg Grundriss der Geschichte, 2020)

Medieval Rules and Customaries Reconsidered - Pansters, Krijn (A Companion to Medieval Rules and Customaries, 2020)

Merovingian Hagiography - Kreiner, Jamie (The Oxford Handbook of the Merovingian World, 2020)

Merovingian Monasticism: Voices of Dissent - Diem, Albrecht (The Oxford Handbook of the Merovingian World, 2020)

Merovingian Religious Architecture: Some New Reflections - Chevalier, Pascale (The Oxford Handbook of the Merovingian World, 2020)

Missions on the Northern and Eastern frontiers, c. 700-1100 - Raaijmakers, Janneke (The Cambridge History of Medieval Monasticism in the Latin West. I. Origins to the Eleventh Century, 2020)

Modern Devotion and Arrangements for Commemoration: Some Observations - Goudriaan, Koen (Inwardness, Individualization, and Religious Agency in the Late Medieval Low Countries. Studies in The 'Devotio Moderna' and its Contexts, 2020)

Monastic art and architecture, c. 700-1100: material and immaterial worlds - Cohen, Adam (The Cambridge History of Medieval Monasticism in the Latin West. I. Origins to the Eleventh Century, 2020)

Monastic canon law in the tenth, eleventh and twelfth centuries - Rolker, Christof (The Cambridge History of Medieval Monasticism in the Latin West. I. Origins to the Eleventh Century, 2020)

Monastic daily life (c. 750–1100): a tight community shielded by an outer court - Cochelin, Isabelle (The Cambridge History of Medieval Monasticism in the Latin West. I. Origins to the Eleventh Century, 2020)

Monastic economics in the Carolingian Age - Devroey, Jean-Pierre (The Cambridge History of Medieval Monasticism in the Latin West. I. Origins to the Eleventh Century, 2020)

Monastic landscapes - Röckelein, Hedwig (The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

Monastic liturgy, 1100–1500: continuity and performance - Boynton, Susan (The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

Monastic preaching and the sermon in medieval Latin Christendom to the twelfth century - Baker, Timothy M.; Kienzle, Beverly (The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

Monastic preaching, c. 1350-1545 - Clark, James; Bush, Kate E. (The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

Monastic reform in the tenth to early twelfth century - Vanderputten, Steven (The Cambridge History of Medieval Monasticism in the Latin West. I. Origins to the Eleventh Century, 2020)

Monastic scriptorium or municipal workshop? - Biemans, Jos A.A.M. (Medieval Documents as Artefacts. Interdisciplinary perspectives on codicology, palaeography and diplomatics, 2020)

Monastic theologies c. 1050-1200 - Mews, Constant J. (The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

Monasticism, reform and authority in the Carolingian Era - Kramer, Rutger (The Cambridge History of Medieval Monasticism in the Latin West. I. Origins to the Eleventh Century, 2020)

Monks and the universities, c. 1200-1500 - Clark, James (.), The Cambridge History of Medieval Monasticism in the Latin West. II. The High and Late Middle Ages, 2020)

Made in Malines. Les statuettes malinoises ou poupées de Malines de 1500-1540. Étude matérielle et typologique - Cayron, Fanny; Steyaert, Delphine (Made in Malines. Les statuettes malinoises ou poupées de Malines de 1500-1540. Étude matérielle et typologique, 2019)

Man on Fire. The Life and Spirit of Norbert of Xanten - Kunkel, Thomas (St. Norbert College Press-Center for Norbertine Studies, 2019)
Populariserend boek

Maubeuge, bâtiments du chapitre des chanoinesses - Baudoux-Rousseau, Laurence (Chanoines et chanoinesses des anciens Pays-Bas. Le chapitre de Maubeuge du IXe au XVIIIe siècle, 2019)

Medical Education in the 12th Century - Jacquart, Danielle (A Companion to Twelfth-Century Schools, 2019)

Medieval and Early Renaissance Building Inscriptionsin the Northern Netherlands - Hartog, Elizabeth den (La pierre comme porteur de messages du chantier de construction et de la vie du bâtiment, 2019)

Memorie en memorandum: De orde van het Gulden Vlies in de Grote Kerk in Den Haag (1456-1545/’46) - Kruip, Marjolein (De Nederlandsche Leeuw, 2019)

Met heiligen en heren langs middeleeuwse parochiekerken. Otto Roemelings gegevensbestand voor Groningen en Drenthe tot omstreeks 1640 - Mol, J.A.(Hans); Langen, Gilles J. de (Groninger Kerken, 2019)
Toelichting op en introductie van de website www.corpusroemeling.nl bevattende alfabetisch en geografisch per parochie opvraagbare gegevens over patoonheiligen, priesters en predikanten, aansluitend bij de cd-rom met data voor Friesland in Roemelings dissertatie uit 2013.

Met maagdelijke blik. De reliekenschat van Herkenrode doorgelicht - Van Cleven, Fanny; Reyniers, Jeroen; Ervynck, Anton (Scienta Artis, 2019)

Methods and Tools of Learning - Weijers, Olga (A Companion to Twelfth-Century Schools, 2019)

Methods of ageing and sexing human dry bone put to the test Looking back on the 1987-1988 excavations in the Broerenkerk in Zwolle - Aten, Nico; Clevis, Hemmy (Osteoarchaeology in historical context. Cemetery research from the Low Countries, 2019)

Modèle monastique. Un laboratoire de la modernité - Dalarun, Jacques (CNRS Éditions, 2019)

Moines et chanoines dans le développement économique et urbanistique de la Cité de Liège au Moyen Âge - Wilkin, Alexis (Moines et chanoines du VIIIe au XVIIIe siècle, 2019)

Molenpatrimonium norbertijnenabdijen BENELUX - Janssens, Herman (Abdijmolens. Natuurkracht ten dienste van norbertijnen en norbertinessen, 2019)
Besteladres: Herman Janssens, Abdijstraat 1, B-3271 Averbode, h.janssens@abdijaverbode.be

The monastic cemetery of the Broederenkerk in Zutphen: For monks only? - Baetsen, Steffen; Groothedde, Michel (Osteoarchaeology in historical context. Cemetery research from the Low Countries, 2019)

Monialen uit het Luikse geslacht Joncis in de abdijen van Nonnemielen en Herkenrode (1549-1781) - Ormelingen, Jean-Jacques van (Limburg. Het Oude Land van Loon, 2019)

Moniales et Sorores: The Canonical Distinction Between Nuns and Sisters With Particular Reference to Benedictine Women Religious - Bauer, Nancy Ann (American Benedictine Review, 2019)

Makelaar tussen Rome en Haasdonk. Antoon van Bourgondië en de Sint-Jacbus-de-Meerdere-broederschap - Verwerft, Bart (Het Land van Beveren, 2018)

The matter of piety. Material culture in Zoutleeuw’s church of Saint Leonard (c. 1450-1620) - Suykerbuyk, Ruben (Department of History, 2018)

Melk, boter, kaas en gevogelte. Een fragment over middeleeuwse diëtetiek - Brakenhoff, Linda (Perkament in stukken. Teruggevonden middeleeuwse handschriftfragmenten, 2018)

Memento mori. Von derSuche nach Gemeinsamkeiten in der Bestattungskultur bis zueiner Grabsteindatenbank - König, Sonja; Schiefer, Paula (Memento Mori. Sterben und Begraben in einen ruralen Grenzgebiet. Sterven en begraven in een rurale grensregio, 2018)

Memoria en gemeeshcapsvorming in de vijftiende eeuw. De getuigenis van het Windesheimers klooster Onze-Lieve-Vrouw Ten Walle te Elsegem bij Oudenaarde - Diemel, Bas (Trajecta, 2018)

Middeleeuws computeren - Waagmeester, Bastiaan; Wassenaar, Jelle (Perkament in stukken. Teruggevonden middeleeuwse handschriftfragmenten, 2018)

Middeleeuwse muzieknotatie in een dodenboek - Verweij, Loni; Pouls, Nick (Perkament in stukken. Teruggevonden middeleeuwse handschriftfragmenten, 2018)

Middeleeuwse nederzettingsvormen langs Demer en Dijle. Het verdwenen dorp en de burcht van Andresbrugge/Andesbrucken (Hansbrug) in de Vita en Adventus van Landoald (980 - 990) en het ontstaan van Haacht en Keerbergen - Minnen, Bart (Haachts oudheid- en geschiedkundig tijdschrift, 2018)

Middeleeuwse nederzettingsvormen langs Demer en Dijle. Het verdwenen dorp en de burcht van Andresbrugge/Andesbrucken (Hansbrug) in de Vita en Adventus van Landoald (980 - 990) en het ontstaan van Haacht en Keerbergen - Minnen, Bart (Haachts oudheid- en geschiedkundig tijdschrift, 2018)

Missaal voor het Sinte-Maria-Magdalenagilde in Brugge - Meulemeester, Jean Luc (Brugse Ommeland, 2018)

Mittelalterliche Priestergrabplatten in Ostfrieslandund im Groningerland - Kroesen, J.E.A. (Memento Mori. Sterben und Begraben in einen ruralen Grenzgebiet. Sterven en begraven in een rurale grensregio, 2018)
Met Nederlandse abstract

The Modern Devout and the Inquisition - Goudriaan, Koen (Ons Geestelijk Erf, 2018)

Monastic Leadership as an ‘Immaterial Resouce’. A Look at Reformist Abbots of the 10th to Early 12th Centuries - Vanderputten, Steven (Klöster und ihre Ressources. Raume und Reformen monastischer Gemeinschaften im Mittelalter, 2018)

Multidisciplinary Study of the Reliquary Contents Attributed to the Bishop Jacques de Vitry (12-13th C. AD) - Polet, Caroline; Carlier, Aurore; Doyen, Lucie; Lebecque, Fiona; Tilleux, Caroline; Bertrand, Benoît; Huchet, Jean-Bernard; Brecko, Jonathan; Strydonck, Mark van (Relics @ the Lab. An Analytical Approach to the Study of Relics, 2018)

Muziek versneden tot dekblad. Acht middeleeuwse handschriftfragmenten met liturgische muzieknotatie - Pouls, Nick; Verweij, Loni (Perkament in stukken. Teruggevonden middeleeuwse handschriftfragmenten, 2018)

The Mystical Fulfilment of a Spiritual Ideal. Common Love in Baldwin of Forde, Beatrice of Nazareth and the Vita Beatricis - Arblaster, John (Ons Geestelijk Erf, 2018)

Mystieke inspiratie uit Groenendaal - Warnar, Geert (De Moderne Devotie. Spiritualiteit en cultuur vanaf de late Middeleeuwen, 2018)

Mystieke vrouwen in Arnhem - Schepers, Kees (De Moderne Devotie. Spiritualiteit en cultuur vanaf de late Middeleeuwen, 2018)

Maagden, weduwen en ander volk - Goudriaan, Koen (Vrouwen en vroomheid. De boetvaardige zusters van het Sint-Ursulaklooster in Purmerend (1392-1572), 2017)

Martelaren van Gorcum. Weerloze slachtoffers van de watergeuzen - Hartmans, Rob (Historisch Nieuwsblad, 2017)

Masters and Schools at St Laurent: Rupert of Deutz and the Scholastic Culture of a Liégeois Monastery - Diehl, Jay (Medieval Liège at the Crossroads of Europe. Monastic Society and Culture, 1000-1300, 2017)
(als e-book: 978-2-503-56897-3)

Medieval Manuscripts. Ghent University Library - Derolez, Albert (Snoeck Ducaju & Zoon, 2017)

The Medieval Military Orders. 1120-1314 - Morton, Nicholas (Seminar studies, 2017)
978-1-138-45168-1 (hardback) en 978-1-4082-4958 (paperback)

Middeleeuwse handschriften uit Groningse kloosters - Feldwerd - As-Vijvers, Anne Margreet W. (Schriftgeheimen. Opstellen over schrift en schriftcultuur, 2017)

Middeleeuwse metadata. Boeken van de Amsterdamse kartuizers - Vlist, Ed van der (Schriftgeheimen. Opstellen over schrift en schriftcultuur, 2017)

Middeleeuwse nederzettingsvormen langs Demer en Dijle . Het verdwenen dorp en de burcht van Andresbrugge/Andesbrucken (Hansbrug) in de Vita en Adventus van Landoald (980 - 990) en het ontstaan van Haacht en Keerbergen - Minnen, Bart (Haachts oudheid- en geschiedkundig tijdschrift, 2017)

Middenrijks Friesland een Markgraafschap? - Winter, Johanna Maria van (Middeleeuwers in drievoud: hun woonplaats, verwantschap en voeding, 2017)

Mirakelen en devotie rond een verkeerde kist? De vermeende stoffelijke resten van Sint Idesbald op de onderzoekstafel - Van Acker, Jan (Madoc, 2017)

Mirakels. Middelnederlandse mirakelcollecties uit de Zuidelijke Nederlanden - Van Mulder, Jonas (Heiligen en tradities in Vlaanderen. Lente en zomer, 2017)

Monks, Aristocrats, and Justice. Twelfth-Century Monastic Advocacy in a European Perspective - West, Charles (Speculum, 2017)

The mulieres religiosae, Daughters of Hildegard of Bingen? Interfaces between a Benedictine Visionary, the Cistercians of Villers, and the Spiritual Women of Liège - Moens, Sara (Medieval Liège at the Crossroads of Europe. Monastic Society and Culture, 1000-1300, 2017)
(als e-book: 978-2-503-56897-3)

Multorum coenobiorum fundator et innumerabilium pater monachorum. Le culte et le souvenir de saint Colomban et de ses disciples dans le Nord de la Gaule du haut Moyen Âge - Mériaux, Charles (L’eredità di san Colombano. Memoria e culto attraverso il Medioevo, 2017)

Macht en goederenbezit van de Van Rodes in het rivierengebied en in Peelland - Bijsterveld, A.J.A. (Rondom Sint-OedenRode. Macht, religie en cultuur in de Meierij, 2016)

Maubeuge et Nivelles à la fin du VIIe siècle: note sur deux passages de la Vita sanctae Aldegundae prima (BHL 244) - Alain Dierkens (Hainaut. La terre et les hommes. Mélanges offerts à Jean-Marie Cauchies par Hannonia à l’occasion de son soixante-cinquième anniversaire, 2016)

Medieval Monasticism. Its History and Forms of Life - Melville, Gert (Cistercian Studies Series, 2016)
Vertaling van Melville, Gert, Die Welt der mittelalterlichen Klöster. Geschichte und Lebensformen (München: C.H. Beck, 2012).

The Memorial Painting which Became a Text Panel. Intended and Actual Functions - Bueren, Truus van; Dijk, Corinne van (Reformations and their Impact on the Culture of Memoria, 2016)
(als e-book 978-2-503-56856-0)

A mirror of princes who opted out: Regino of Prüm and royal monastic conversion - Goosmann, Erik; Meens, Rob (Religious Franks. Religion and Power in the Frankish Kingdoms: Studies in Honour of Mayke de Jong, 2016)

Monastische Reformen im Zeitalter des Investiturstreits und ihre Resonanz im Rhein-Maasraum. Der Liber officii Capituli des St. Viktor-Stifts Xanten (Cod. Monast. 101) und sein historischer Zeugniswert - Lieven, Jens (Reformations and their Impact on the Culture of Memoria, 2016)
(als e-book 978-2-503-56856-0)

Muziek voor Sint-Oda. Officie en mis uit twee gregoriaanse koorboeken van de Sint-Jan in ‘s-Hertogenbosch - Roelvink, Véronique (Rondom Sint-OedenRode. Macht, religie en cultuur in de Meierij, 2016)

The Making and Meaning of the Liber Floridus. A Study of the Original Manuscript, Ghent, University Library, MS 92 - Derolez, Albert (Studies in Medieval and Early Renaissance Art History, 2015)

Manuscript and Memory in Religious Communities in the Medieval Low Countries. An Introduction - Deploige, Jeroen; Nip, Renée I.A. (The Medieval Low Countries, 2015)

Manuscript Communication. Visual and Textual Mechanics of Communication in Hagiographical Texts from the Southern Low Countries, 900-1200 - Snijders, Tjamke (Utrecht Studies in Medieval Literacy, 2015)

The Marian Dimension to the First Executions of the Reformation - Christman, Robert (Church History and Religious Culture, 2015)
Mariale dimensie bij de eerste protestanten op de brandstapel, de augustijner monniken Hendrik Voes en Jan van den Esschen te Brussel in 1523

Mathilde de Toscane/Canossa et les monastères fondés entre les Ardennes et l’Italie du Nord du temps de son premier mariage - Golinelli, Paolo (Les origines de l’abbaye cistercienne d’Orval. Actes du colloque organisé à Orval le 23 juillet 2011, 2015)

Medieval Studies in The Catholic Historical Review - Constable, Giles; Bruce, Scott G. (Catholic Historical Review, 2015)

Memoria für die Zukunft. Zur Gestaltung von Erinnerung in den Schwesternbüchern der Devotio moderna - Bollmann, Anne M. (The Medieval Low Countries, 2015)

Memory and Manuscript in Personal Practice and Written Lives. The Case of the Modern-Day Devout - Engen, John van (The Medieval Low Countries, 2015)

Memory and Reward. Dutch Collections of Sermons and their Functions in the Memoria Tradition in the Female Convent of Jericho in Brussels (c. 1450-1650) - Stoop, Patricia; Mertens, Thom (The Medieval Low Countries, 2015)

Monastic Cartularies, Institutional Memory and the Canonization of the Past. The Two Libri Traditionum of St Peter’s Abbey, Ghent - Declercq, G. (The Medieval Low Countries, 2015)

Monniken, studenten en soldaten - Verbaal, Wim M. (Geloven in Gent. Plaatsen van het religieuze verleden, 2015)
Deze bijdrage behandelt de Sint-Pietersbenedictijnenabdij.

Monument voor de eeuwigheid - Schmidt, Peter (Geloven in Gent. Plaatsen van het religieuze verleden, 2015)
Deze bijdrage betreft de Sint-Jansparochiekerkl, vanaf 1559 Sint-Baafskathedraal.

Moord of wettige zelfverdediging? Geestelijke uit Ieper doodt twee jongelingen met messteken in Boezinge, 23 maart 1558 (n.s.) - Desreumaux, John (Westhoek, 2015)

Muurschilderingen in de dominicanenkerk te Maastricht - Zilverschoon, Jacoline (Madoc, 2015)

Maastricht en de Nederlandse literatuur in de Middeleeuwen - Scheepsma, Wybren F. (De Maasgouw, 2014)

Memories of the preaching for the Fifth Crusade in Caesarius of Heisterbach's Dialogus miraculorum - Purkis, William J. (Journal of Medieval History, 2014)

Met het oog op het Laatste Oordeel. De geboorte van het individu in de westerse kunst - Vries, Dirk J. de (Clavis Kleine Kunsthistorische Monografieën, 2014)

Middeleeuwse muurschilderingen in de Bergkerk in Deventer - Rijn, Elselien van (Analecta Praemonstratensia, 2014)

The Mind as Cell and the Body as Cloister. Abbatial Leadership and the Issue of Stability in the Early Eleventh Century - Vanderputten, Steven (Innovationen durch Deuten und Gestalten. Klöster im Mittelalter zwischen Jenseits und Welt, 2014)

My cell is my castle. Variaties op kloosterlijke huiselijkheid, 5de-9de eeuw - Diem, Albrecht (Holland, 2014)

Mysticism in the Low Countries Before Ruusbroec - Arblaster, John; Faesen, Rob (A Companion to John of Ruusbroec, 2014)

Mystieke antropologie in het zestiende-eeuwse traktaat Vanden tempel onser sielen - Nie, Renske van (Handelingen van de Koninklijke Zuid-Nederlandse Maatschappij voor Taal- en Letterkunde en Geschiedenis, 2014)

Macht, geweld en monniken, De escalatie van een vete in de Friese Zuidwesthoek 1482–1495 - Gerrits, M.; Mol, J.A.(Hans) (De Vrije Fries, 2013)
Betreft de abdij van Staveren en de proosdij van Hemelum

Magister Nicolaus, Gerardus, Frater Hugo et autres orfèvres connus-inconnus. À propos de la croix de l'empereur Henri à Venise et de celle de l'abbé Hugues de Laon - Didier, Robert (Actes de la journée d'étude Hugo d'Oignies. Contexte et perspectives, 2013)

Manuscript Production in a Carmelite Convent: The Case of Cornelia von Wulfskercke - As-Vijvers, Anne Margreet W. (Books of Hours Reconsidered, 2013)

Martyrs, relics and holy places: the christianization of the countryside in the Archdiocese of Rheims during the Meroginvian Period - Meijns, Brigitte L.I. (Paganism in the Middle Ages. Threat and Fascination, 2013)

Medieval Libraries in the Low Countries. Thoughts for an Integrated Approach - Derolez, Albert (Queeste, 2013)

Memoria et Caritas. Jaargetijden als armenzorg in de Onze-Lieve-Vrouweparochie te Gent in de late middeleeuwen - Franck, Hannelore (Handelingen der Maatschappij voor Geschiedenis en Oudheidkunde te Gent, 2013)

Middeleeuwse strafbedevaarten vanuit Leuven - Ceunen, Marika (Clavis Scabinorum, 2013)
De publicatie is te verkrijgen bij het Stadsarchief Leuven, Rijschoolstraat 4 te 3000 Leuven.

Middeleeuwse vitae. Leugens om bestwil? - Janssens, Jozef D. (Sint-Guido van Anderlecht. Eeuwen van volksdevotie, 2013)
Te verkrijgen bij het Archief en Museum voor het Vlaams Leven te Brussel, Arduinkaai 28, 1000 Brussel, http://www.amvb.be/

Monastic Reform as Process: Realities and Representations in Medieval Flanders, 900–1100 - Vanderputten, Steven (Cornell University Press, 2013)
The history of monastic institutions in the Middle Ages may at first appear remarkably uniform and predictable. Medieval commentators and modern scholars have observed how monasteries of the tenth to early twelfth centuries experienced long periods of stasis alternating with bursts of rapid development known as reforms. Charismatic leaders by sheer force of will, and by assiduously recruiting the support of the ecclesiastical and lay elites, pushed monasticism forward toward reform, remediating the inevitable decline of discipline and government in these institutions. A lack of concrete information on what happened at individual monasteries is not regarded as a significant problem, as long as there is the possibility to reconstruct the reformers' 'program.'’ While this general picture makes for a compelling narrative, it doesn’t necessarily hold up when one looks closely at the history of specific institutions. In Monastic Reform as Process, Steven Vanderputten puts the history of monastic reform to the test by examining the evidence from seven monasteries in Flanders, one of the wealthiest principalities of northwestern Europe, between 900 and 1100. He finds that the reform of a monastery should be studied not as an "exogenous shock" but as an intentional blending of reformist ideals with existing structures and traditions. He also shows that reformist government was cumulative in nature, and many of the individual achievements and initiatives of reformist abbots were only possible because they built upon previous achievements. Rather than looking at reforms as "flashpoint events," we need to view them as processes worthy of study in their own right. Deeply researched and carefully argued, Monastic Reform as Process will be essential reading for scholars working on the history of monasteries more broadly as well as those studying the phenomenon of reform throughout history.

Mysticism with or without the Church? John of Ruusbroec's conflict with the Clergy - Arblaster, John; Faesen, Rob (International Journal of Philosophy and Theology, 2013)

Manuscripts from Zutphen, Lamb of God Roundels, and en New Iconography of Penance - Rudy, Kathryn M. (Quaerendo, 2012)

Margaretha van Antiochië (Margaretha van Scheluinen) - Reesing, Ingmar (Middeleeuwse beelden uit Utrecht. 1430-1530, 2012)
Mogelijk comanderij van de Duitse orde te Schelluinen

Maria met Kind - Reesing, Ingmar (Middeleeuwse beelden uit Utrecht. 1430-1530, 2012)
Emmanuelshuizen (Zwolle)

Master Wiger of Utrecht's Liber exemplorum sub titulis redactorum - Winter, David Ross (Journal of Medieval History, 2012)

Mehr als neunhundert Jahre Bücher. Das St. Viktor-Stift und seine Bibliotheken - Tervooren, Helmut (Das St. Viktor-Stift Xanten. Geschichte und Kultur im Mittelalter, 2012)

Memorie van een vrome vrouw en eerbiedwaardig abt in woord en beeld. Het (Kopenhaagse) leven van Lutgart in Affligem omstreeks 1265 - Mantingh, Erwin (Eigen Schoon en de Brabander, 2012)

Middeleeuwse handschriften uit Groningse kloosters – een kwart eeuw later - As-Vijvers, Anne Margreet W. (Illuminatie, illustratie, boekband & bibliotheek in de Noordelijke Nederlanden. Liber amicorum Jos.M. Hermans († 2007), 2012)

Middeleeuwse pastorieën in Groningen: een inleiding - Kuiken, Cornelis Jan (Groninger Kerken, 2012)

Monastic Recruitment in an Age of Reform: New Evidence for the Flemish Abbey of Saint Bertin (10th-12th centuries) - Vanderputten, Steven (Revue bénédictine, 2012)

Monastic Reform, Abbatial Leadership and the Instrumentation of Cluniac Discipline in the Early Twelfth-Century Low Countries - Vanderputten, Steven (Revue Mabillon, 2012)

Monniken buiten de abdij. De proosdijen van de Paulusabdij op de Heiligenberg en in Driel - Vliet, Kaj van (De nalatenschap van de Paulusabdij in Utrecht, 2012)

Morele en juridische beschouwingen rond duel, toernooi en oorlog door Arnold Gheyloven van Rotterdam (c. 1375-1442) in zijn Gnotosoltos sive Speculum conscientiae - Weiler, Anton G. (Trajecta, 2012)

Magister Anselmus Fabri van Breda en de stichting van een gasthuis voor oude mannen aan de Haagdijk te Breda in 1455. Deel 3: Het functioneren van zijn netwerk in de regio Breda-Gilze-Zundert vóór en na zijn overlijden in 1449 - Gooskens, Frans A. (Jaarboek van de Geschied- en Oudheidkundige Kring van Stad en Land van Breda ‘De Oranjeboom’, 2011)

Manière de la fondation et augmentation de l’église Notre-Dame de Boulogne - Schandel, Pascal (Vlaamse Miniaturen. 1404-1482, 2011)

The meeting of chant and polyphony in monophonic square notation from Cambrai Cathedral 1250-1550 - Haggh, Barbara (The Calligraphy of Medieval Music, 2011)

Memor esto mei. Devotional Diptychs and Religious Orders in the Late Medieval Low Countries - Engen, Hildo van (Living Memoria. Studies in Medieval and Early Modern Memorial Culture in Honour of Truus van Bueren, 2011)

Memoria and Amende Honorable in the Utrecht Collegiate Chapter of St. Mary - Hoven van Genderen, Abraham Jacobus (Bram) van den (Living Memoria. Studies in Medieval and Early Modern Memorial Culture in Honour of Truus van Bueren, 2011)

Metra de Morte. Eine lateinische Totenklage über den verstorbenen Graf Guy von Blois (1397), als Teil der sich entwickelnden Memoriakultur - Boer, Dick E.H. de (Living Memoria. Studies in Medieval and Early Modern Memorial Culture in Honour of Truus van Bueren, 2011)

Middeleeuwse kerken in Groningen en Ostfriesland - Kroesen, J.E.A. (Groninger Kerken, 2011)

Middeleeuwse sporen van Utrechtse pelgrims naar Santiago - Vervaart, Otto (Oud-Utrecht, 2011)

Mise à jour d'une partie d'un ancien cloître de l'abbaye Notre-Dame de Saint-Remy à Rochefort (province de Namur) - Frébutte, Christian; Tilmant, Pierre-Hugues (Archaeologia mediaevalis, 2011)

Monachisme et aristocratie aux Xe-XIe siècles. Un regard sur l’historiographie récente - Mazel, Florian (Ecclesia in medio nationis. Reflections on the Study of Monasticism in the Central Middle Ages. Réflexions sur l’étude du monachisme au moyen âge central, 2011)

The Monastic World View in the Artistic Tradition - Reilly, Diane (Ecclesia in medio nationis. Reflections on the Study of Monasticism in the Central Middle Ages. Réflexions sur l’étude du monachisme au moyen âge central, 2011)

Mongol inhospitality, or how to do more with less? Gift giving in William of Rubruck’s Itinerarium - Watson, A.J. (Journal of Medieval History, 2011)

Monniken in het moeras. De vroegste geschiedenis van de abdij van Sint-Laurens in het Oostbroek bij Utrecht - Broer, Charlotte J.C. (Dr. C.J.C. Broer, Stationlaan 41 NL-3583 RB Utrecht / cjcbroer@casema.nl, 2011)

A Monument to a Glorious Past and a Questionable Future? The Jerusalem Chapel in Bruges and its Stained Glass Windows - Dikken, Charlotte (Living Memoria. Studies in Medieval and Early Modern Memorial Culture in Honour of Truus van Bueren, 2011)

Mousty. Les origines: thèses et hypothèses - De Bock, Sébastien (Wavriensia, 2011)

Musicologische verkenning vanuit het Antifonarium Tsgrooten (1522) - Mannaerts, Pieter (Premonstratenzer gregoriaans in de Nederlanden: Liturgische handschriften (13de-16de eeuw), 2011)
63p. geen ISBN Besteladres: Herman Janssens, Abdij 1, B-3271 Averbode, h.janssens@abdijaverbode.be

The Mystical Dimension in Flemish Primitive Painting. Exploring the Spiritual Affinity between John of Ruusbroec and Rogier van der Weyden - Bekaert, Edward (Ons Geestelijk Erf, 2011)

Magister Anselmus Fabri van Breda en de stichting van een gasthuis voor oude mannen aan de Haagdijk te Breda in 1455. Deel 2: Het ontstaan van apostelhuizen in Brabant en het Rijnland - Gooskens, Frans A. (Jaarboek van de Geschied- en Oudheidkundige Kring van Stad en Land van Breda ‘De Oranjeboom’, 2010)

Manors and Markets: Economy and Society in the Low Countries 500-1600 - Bavel, Bas J.P. van (Oxford University Press, 2010)

Material Restoration. A Fragment from Eleventh-Century Echternach in a Nineteenth-Century Parisian Codex - Vircillo Franklin, Carmela (Cursor Mundi, 2010)

Meurtre politique, guerre civile et catharsis littéraire au XIIe siècle. Les émotions dans l'oeuvre de Guibert de Nogent et de Galbert de Bruges - Deploige, Jeroen (Politiques des émotions au Moyen Âge, 2010)

Middeleeuwse verering van de Heilige Dimpna in Geel - Alain Dierkens; Finoulst, Laure-Anne; Lambot, Stéphanie (Geschiedenis der geneeskunde, 2010)

Middeleeuwse visies op visio spiritualis: ontwikkeling van theorieën en praktijken in mystieke middens, met Hadewijch als vluchtpunt - Fraeters, Veerle (De letter levend maken. Opstellen aangeboden aan Guido de Baere bij zijn zeventigste verjaardag, 2010)

Monastères et scriptoria en Lotharingie (IXe - Xe siècles) - Schneider, Jens (Handelingen van de Koninklijke Commissie voor Geschiedenis, 2010)

Mons (Ht): surveillance archéologique dans le chœur de la collégiale Sainte-Waudru - Dumont, Gaëlle (Archaeologia mediaevalis, 2010)

Mur du couvent des Croisiers redécouvert à Dinant, "en ile" (Nr.) - Verbeek, Marie; Saint-Amand, Pascal (Archaeologia mediaevalis, 2010)

Mystiek op schrift in vrouwenkloosters uit de traditie van de Moderne Devotie. Een oriënterende vergelijking van drie collecties: Arnhem, Geldern en Maaseik - Kienhorst, Hans (Ons Geestelijk Erf, 2010)

Machtanspruch und Memoria. Die Bedeutung Graefenthals im Zentrum des Herzogtums Geldern - Frankewitz, Stefan (Graefenthal. Ein Kloster der Zisterzienserinnen am Niederrhein, 2009)

Manuscript Layout and Réécriture. A Reconstruction of the Manuscript Tradition of the Vita Secunda Gisleni - Snijders, Tjamke (Belgisch Tijdschrift voor Filologie en Geschiedenis, 2009)

On the Margins of Religious Life: Hermits and Recluses, Penitents and Tertiaries, Beguines and Beghards - Simons, Walter (Christianity in Western Europe, c. 1100-c. 1500, 2009)

Material support I: parishes - Resl, Brigitte (Christianity in Western Europe, c. 1100-c. 1500, 2009)

Material support II: religious orders - Burton, Janet (Christianity in Western Europe, c. 1100-c. 1500, 2009)

Medieval letters and letter collections as historical sources: methodological questions and reflections and research perspectives (6th-14th centuries) - Ysebaert, Walter (Studi Medievali, 2009)

Memory and Witness: “Translated Images” - Ciulisova, Ingrid (Belgisch Tijdschrift voor Oudheidkunde en Kunstgeschiedenis, 2009)

Misbruik en devaluatie van excommunicatie in het Merovingische Rijk - Keygnaert, Frederik (Jaarboek voor Middeleeuwse Geschiedenis, 2009)

Monastic and religious orders, c. 1100-c. 1350 - McGuire, Brian Patrick (Christianity in Western Europe, c. 1100-c. 1500, 2009)

Monks, Knights, and the Enactment of Competing Social Realities in Eleventh- and Early-Twelfth-Century Flanders - Vanderputten, Steven (Speculum, 2009)

Mother of God: a history of the Virgin Mary - Rubin, Miri (Allen Lane, 2009)

The Maastricht 'ordinarii custodum'. Rare Exponents of a Little-Known Genre - Dückers, Rob (Manuscript Studies in the Low Countries. Proceedings of the "Groninger Codicologendagen" in Friesland, 2002, 2008)

The making of a minor saint in Drogo of Saint-Winnoc’s Historia translationis s. Lewinnae - Defries, D. (Early Medieval Europe, 2008)

A manuscript of Petrus Dorlandus of Diest's Viola animae - Doyle, A.I. (Studies in Carthusian monasticism in the late Middle Ages, 2008)

Martyrdom, Murder, and Magic. Child Saints and their Cults in Medieval Europe - Wasyliw, Patricia Nealy (Studies in Church History, 2008)

Matriculae, xenodochia, hospitalia und Leprosenhäuser im Frühmittelalter - Irsigler, Franz (Institutions de l’assistance sociale en Lotharingie médiévale. Actes des 13es Journées Lotharingiennes. Luxembourg, 12-15 octobre 2004, 2008)

Medieval Brick Architecture in Flanders and Northern Europe. The Question of the Cistercian Origin - Coomans, Thomas; Royen, Harry van (Medieval Brick Architecture in Flanders and Northern Europe. The Question of the Cistercian Origin, 2008)

Metaphors of Transcendence and Transformation in the Arnhem Mystical Sermons (Royal Library, The Hague, ms. 133 H 13). Moses’ Ascent of Mount Sinai as an Allegory for Mystical Experience - Cornet, Ineke (Ons Geestelijk Erf, 2008)

A Miracle of Jonatus in 1127. The Translatio S. Jonati in Villa Saliacensi (BHL 4449) as Political Enterprise and Failed Hagiographical Project - Vanderputten, Steven (Analecta Bollandiana, 2008)

Monastiek observantisme en Moderne Devotie in de Noordelijke Nederlanden - Engen, Hildo van; Verhoeven, Gerrit (Monastiek observantisme en Moderne Devotie in de Noordelijke Nederlanden, 2008)

Monnaies provenant du site de l'ermitage Saint-Thibaut à Marcourt (arr. Marche-en-Famenne, province de Luxembourg) - Dengis, Jean-Luc (Revue belge de numismatique et de sigillographie, 2008)

More Manuscripts from Mariënwater? Manuscript Production in a Birgittine Convent Reconsidered - Dongen, Gerrie A.M. van (Manuscript Studies in the Low Countries. Proceedings of the "Groninger Codicologendagen" in Friesland, 2002, 2008)

Multiple Options: The World of the Fifteenth-Century Church - Engen, John van (Church History, 2008)

Music and Meditation: Songs in Johannes Mauburnus’s Rosetum exercitiorum spiritualium - Hascher-Burger, Ulrike (Church History and Religious Culture, 2008)

Music for Canons, Emperors, Dukes and Prince Bishops in the Collegiate Church of Maastricht (c. 1450–1520). An Updated Overview and Some Samples - Schreurs, Eugeen (Yearbook of the Alamire Foundation, 2008)

Magister Anselmus Fabri van Breda en de stichting van een gasthuis voor oude mannen aan de Haagdijk te Breda in 1455. Zijn carrière te Rome (1402-1449) - Gooskens, Frans A. (Jaarboek van de Geschied- en Oudheidkundige Kring van Stad en Land van Breda ‘De Oranjeboom’, 2007)

Magister Egidius van Brugge en de Ninoofse abdij - Van de Perre, Dirk (Het Land van Aalst, 2007)

The medieval abbey of Herkenrode. New evidence from the archaeological investigations - Smeets, Maarten (Zisterzienser im Norden. Neue Forschungen zur Klosterarchäologie. Symposium bei der Ostfriesischen Landschaft in Aurich vom 19. - 20. Oktober 2006, 2007)

Meer mystiek uit het Arnhemse Agnietenklooster: de handschriften Den Haag, Koninklijke Bibliotheek, 71 H 51 en 133 H 13 - Kienhorst, Hans (Manuscripten en miniaturen. Studies aangeboden aan Anne S. Korteweg bij haar afscheid van de Koniklijke Bibliotheek, 2007)

Meester Arnoud en het stenen monster - Leenders, K.A.H.W. (Jaarboek van de Geschied- en Oudheidkundige Kring van Stad en Land van Breda ‘De Oranjeboom’, 2007)
Gaat in op de achtergronden van een oorkonde uit 1269 waarin sprake was van een stenen kerk te Breda. In de akte is er sprake van een meester Arnoud van Coevorden. Er wordt gepoogd in deze bijdrage de persoon van meester Arnoud beter te plaatsen onder andere door een onderzoek naar de toponiem Coevorden.

Microanalyse van middeleeuwse bouwwerven. De steenhouwchronologie toegepast op de kerken van Anderlecht en Vivloorde (Br. en Vl. Brab.) - Doperé, Frans (Archaeologia mediaevalis, 2007)

Middelnederlandse bewerkingen van het passieverhaal: Van informatiebron tot meditatietekst - van Aelst, José (Middelnederlandse bijbelvertalingen, 2007)

Middelnederlandse Levens van Jezus: "Uuten .iiii. ewangelisten ene evangelie ghemaect" - Hollander, August den (Middelnederlandse bijbelvertalingen, 2007)

Middelnederlandse psaltervertalingen: "Het is nergens voor nodig om veel meer boeken dan het psalter te bestuderen" - Desplenter, Youri (Middelnederlandse bijbelvertalingen, 2007)

The Migration of Ideas in the Early Middle Ages: Ways and Means - McKitterick, R. (Foundations of Learning: The Transfer of Encyclopaedic Knowledge in the Early Middle Ages, 2007)

Miracles and Wonders. The Development of the Concept of Miracle, 1150-1350 - Goodich, Michael E. (Church, Faith and Culture in the Medieval West, 2007)

Monasteri e ordini religiosi nella struttura ecclesiastica: Osservationi e problematiche circa la posizione giuridica e i rapporti istituzionali tra metà XI e metà XII secolo - Cariboni, Guido (Mittelalterliche Orden und Klöster im Vergleich. Methodische Ansätze und Perspektiven, 2007)

Muziek en muziektheorie in handschriften uit Ten Duinen en Ter Doest - Mannaerts, Pieter (Novi Monasterii, 2007)

Magnus is de naam. De transformatie van een heilige in de Friezenkerk in Rome - Brouwer, Tiemen (Tijdschrift voor Nederlandse Kerkgeschiedenis, 2006)

The Manuscript Transmission of the Vita Mariae Oigniacensis in the Later Middle Ages - Folkerts, Suzan (Mary of Oignies. Mother of Salvation, 2006)

Mary of Oignies. A Friend to the Saints - Bolton, Brenda M. (Mary of Oignies. Mother of Salvation, 2006)

Matthieu Grenet (1452-1503), bénédictin et écrivain à Saint-Martin de Tournai. Sa vie et son oeuvre - De Grieck, Pieter-Jan (Revue bénédictine, 2006)

Men and Women of the Hospitaller, Templar and Teutonic Orders: Twelfth to Fourteenth Centuries - Tommasi, Francesco (Hospitaller women in the Middle Ages, 2006)

Mort et pouvoir: le choix du lieu de sépulture (espace Meuse-Moselle, XIe-XIIe siècles) - Margue, Michel (Sépulture, mort et représentation du pouvoir au moyen âge, 2006)

Mort et sépulture des comtes de Hainaut jusqu'en 1195 - De Waha, Michel; Dugnoille, Jean (Sépulture, mort et représentation du pouvoir au moyen âge, 2006)

Maiestas Domini. Une image de l’Église en Occident (Ve-IXe siècles) - Poilpré, Anne-Orange (Cerf histoire, 2005)

Managing tithes in the late middle ages - Dodds, Ben (The Agricultural History Review, 2005)

Mannenregels voor een vrouwenwereld. De spirituele opvoeding van zusters in derde-ordegemeenschappen - Corbellini, Sabrina (Trajecta, 2005)

Medieval Letter-Collections as a Mirror of Circles of Friendship? The Example of Stephen of Tournai. 1128-1203 - Ysebaert, Walter (Belgisch Tijdschrift voor Filologie en Geschiedenis, 2005)

Medieval Narrative Sources: A Fascinating Gateway into the Medieval Mind - Milis, Ludo J.R. (Medieval Narrative Sources. A Gateway into the Medieval Mind, 2005)

Medieval religion: new approaches - Berman, Constance H. (Re-Writing Histories, 2005)

Meester Ewolt. Deventer schilder in de zestiende eeuw - Stein-Wilkeshuis, Martina (Overijsselse historische bijdragen, 2005)

Met de zodiak op drift. Structuur en 'stemmen' in Jan van Leeuwens «Vanden seven teekenen der sonnen» - Reynaert, Joris (Queeste, 2005)

Met het volste recht. De juridische pretenties van de tertiarissen van het Kapittel van Utrecht - Engen, Hildo van (Trajecta, 2005)

Middeleeuwse aflaten en Nederlandse devotie - Herwaarden, Jan van (Een profane pelgrimage naar de Middeleeuwen. Opstellen van prof. dr. Jan van Herwaarden over geloof en samenleving in de laatmiddeleeuwse Nederlanden, 2005)

Mijnkin van Kortrijk en heilige anorexie. 1445-1450 - Vleeschouwers-Van Melkebeek, Monique (De Leiegouw, 2005)

Model reading: saints' lives and literature of religious formation in the eleventh and twelfth centuries - Spijker, Ineke van 't ('Scribere sanctorum gesta'. Recueil d’études d’hagiographie médiévale offert à Guy Philippart, 2005)

Moniales cisterciennes et mémoire dynastique: églises funéraires princières et abbayes cisterciennes dans les anciens Pays-Bas médiévaux - Coomans, Thomas (Cîteaux. Commentarii Cistercienses, 2005)

Monnikhuizen. Monichusen - Goder, Harald (Monasticon Cartusiense, 2005)

Mons. L'ancienne collégiale Sainte-Waudru - Piérard, Christiane (Le Patrimoine médiéval de Wallonie, 2005)

Music and liturgy in Sint Janskerk in Gouda - Biermans, Marloes (The Seventh Window. The King’s Window donated by Philip II and Mary Tudor to Sint Janskerk in Gouda (1557), 2005)

Musical relations between the court and collegiate chapels in the Netherlands, 1450-1560 - Schreurs, Eugeen (The Royal Chapel in the time of the Habsburgs: Music and court ceremony in early modern Europe, 2005)

Musik in der Architektur. Von der Antike zum Mittelalter - Heinz, Werner (Beihefte zur Mediaevistik, 2005)

Muziekhandschriften van Soeterbeeck - Boogaerts, J.G.P.G. (Rijkdom in eenvoud. Laatmiddeleeuwse handschriften uit klooster Soeterbeeck, 2005)

Maria doctrix. Anachoretic Women, the Mother of God, and the Transmission of Knowledge - Mulder-Bakker, Anneke B. (Seeing and Knowing. Women and Learning in Medieval Europe, 1200-1550, 2004)

Martyrdom and memory: early Christian culture making - Castelli, Elizabeth A. (Columbia University Press, 2004)

Masculinizing Religious Life: Sexual Prowess, the Battle for Chastity and Monastic Identity - Murray, Jacqueline (Holiness and masculinity in the Middle Ages, 2004)

Medieval pilgrim badges and their iconographic aspects - Kroon, Marike De (Art and architecture of late medieval pilgrimage in Northern Europe and England, 2004)

Medieval religious women in the Low Countries : the "modern devotion", the Canonesses of Windesheim and their writings - Scheepsma, Wybren F. (Boydell Press, 2004)

Meesters met noodnamen - Liebergen, Léon van (Kunstschrift, 2004)
Bijdrage in het themanummer Eik en linde. Houten beelden uit de late middeleeuwen

Memoria ou damnatio memoriae? L'image de Gislebert, duc de Lotharingie († 939) - Alain Dierkens; Margue, Michel (Retour aux sources. Textes, études et documents d'histoire médiévale offerts à Michel Parisse, 2004)

Middeleeuwse beeldhouwkunst op zegels. Het voorbeeld van het conventszegel van de abdij Vrouwenpark (Rotselaar, prov. Vlaams-Brabant) - Minnen, Bart (Belgisch tijdschrift voor numismatiek en zegelkunde, 2004)

Middeleeuwse zandstenen grafkisten uit Westerlauwers Friesland - Kuiken, Cornelis Jan (De Vrije Fries, 2004)

Middelnederlandse pelgrimages, hoever en waarheen? Een verkenning - Biesheuvel, Ingrid (Op reis met Memoria, 2004)

Misgivings about Miracles in Carolingian Hagiography from Utrecht - Egmond, Wolfert S. van (Miracles and the miraculous in medieval Germanic and Latin literature, 2004)

Moergestel tussen 1147 en 1392. De vorming van een Brabantse heerlijkheid - Leenders, K.A.H.W. (Brabants Heem, 2004)
Hoe het Luikse Sint-Janskapittel uit Moergestel buitengewerkt wordt.

Moines, chanoines et religieux au Moyen Âge. Guide de recherche et documents. - Vauchez, André; Caby, Cécile (L'Atelier du Médiéviste, 2004)

Mons: La collégiale Sainte- Waudru - Piérard, Christiane; Lecocq, Isabelle (Le patrimoine exceptionnel de Wallonie, 2004)

Martini. Kerk en toren - Werff, E.O. van der (Noordboek, 2003)

Middeleeuws Leusden in bisschoppelijke rekeningen - Verduin, J. (Fonds Publicaties Geschiedenis Leusden, 2003)

Mysticism and Modern Devotion. Alijt Bake's (1415-1455) Lessons in the Mystical Way of Living - Scheepsma, Wybren F. (Spirituality renewed. Studies on the Significant Representatives of the Modern Devotion, 2003)

Machtsstrijd in Hamaland. De politieke ambities van Balderik en Adela, circa 973-1016 - Kos, Anton (Jaarboek voor Middeleeuwse geschiedenis, 2002)

'Media vita in morte sumus'. Graven als representatie van sociale structuren - Bossuyt, Stijn (In de voetsporen van Jacob van Maerlant. Liber amicorum Raf De Keyser. Verzameling opstellen over middeleeuwse geschiedenis en geschiedenisdidactiek, 2002)

Medicijnen en muziek. Egmondse kloosterrekeningen uit de zestiende eeuw als bron voor medische geschiedenis en muziekgeschiedenis in het noorden van Holland - Vis, G.N.M. (Boeken en handschriften uit Egmond. De abdij van Egmond. Geschreven en beschreven, 2002)

Meer dan glazen alleen - Eck, A van; Mijnlieff, Ewoud M.; Klein, Jan Willem E.; Goudriaan, Koen; Berg, Bianca van den (Duizend jaar Gouda. Een stadsgeschiedenis, 2002)

Met de dood voor ogen. Leven met het hiernamaals in middeleeuws Groningen - Schaïk, Remi van (Groninger Kerken, 2002)

Mijn wijsheid in een boek. Over het verzamelen van kennis - Karen De Coene (Meesterlijke Middeleeuwen. Miniaturen van Karel de Grote tot Karel de Stoute, 800-1475, 2002)

'Mijt dijt spynnen soe suldi den hemel gewinnen'. Die Arbeit als normierender und frömmigkeitszentrierender Einfluß in den Frauengemeinschaften der Devotio moderna - Bollmann, Anne M. (Normative Zentrierung, 2002)

Monastieke spiritualiteit - Cahn, Walter (Meesterlijke Middeleeuwen. Miniaturen van Karel de Grote tot Karel de Stoute, 800-1475, 2002)

Manuel de réforme intérieure. Tractatus devotus de reformacione virium anime - Legrand, F.; van Aelst, José (Sous la règle de saint Augustin, 2001)
Keywords: Tekstuitgave

The Medieval Burial Ground Surrounding Saint Peter's Minster of Leuven (B.). The Archeological Excavation in 1997 - Vandekerchove, Veronique (Belgian Archaeology in a European Setting. Album amicorum Prof. J.R. Mertens (°1921), 2001)

Monastische Reform zwischen Person und Institution. Zum Wirken des Abtes Adam Meyer von Gross St. Martin in Köln (1454-1499) - Hammer, Elke-Ursel (Studien zur Germania Sacra, 2001)

Muurschilderkunst in Nedersaksen, Bremen en Groningen. Vensters op het verleden - Grote, Rolf-Jürgen; Ploeg, Kees van der (Niedersaksisches Landesambt für Denkmalplfege-Stichting Oude Groninger Kerken, 2001)

Macht en gezag in het Markiezaat. Een politiek-institutionele studie over stad en land van Bergen-op-Zoom (1477-1583) - Ham, Wilhelmus Adriaan van (Verloren, 2000)

Margriete van Hemsrode, een vermeende priorin in het hospitaal (1232) - Castelain, Rik (Handelingen van de Geschied- en Oudheidkundige Kring van Oudenaarde, 2000)

Meester Jacob de Pape (Poperinge c. 1480 – Ieper c. 1555), priester, schoolrector, dichter, auteur van historische evocaties en pleitbezorger van het Iepers armenreglement - Schoonaert, Germain (Westhoek, 2000)

Monumenta Arroasiensia - Tock, Benoît-Michel; Milis, Ludo J.R. (Corpus Christianorum Continuatio Mediaevalis, 2000)

Mors certa, hora incerta. De zorg voor de doden bij de lekenbroeder- en zustergemeenschappen te Leiden in de late Middeleeuwen - Luijk, Madelon van (Holland, regionaal-historisch tijdschrift, 2000)

Musique et rituel à l'abbaye Saint-Bavon: structure et développement du rituel, le chant, les livres du rite et les imprimés - Haggh, Barbara (La Cathédrale Saint-Bavon de Gand du moyen âge au baroque, 2000)

Muziek en ritueel in de Sint-Baafsabdij: structuur en ontwikkeling van de liturgie, het Gregoriaans, de liturgische handschriften en drukken - Haggh, Barbara (De Sint-Baafskathedraal in Gent: van Middeleeuwen tot barok, 2000)

Magister consensus. Wessel Gansfort (1419-1489) und die Geistliche Kommunion - Caspers, Charles M.A. (Northern humanism in European context, 1469-1625. From the ‘Adwert Academy’ to Ubbo Emmius, 1999)

Middeleeuwse bronnen van het Luikse 'Leven van Jezus' - Hollander, August den; Schmid, Ulrich (Queeste, 1999)

Middeleeuwse premonstratenzer sites en kerken in België - Vander Laenen, Frederik; Van de Perre, Dirk (Middeleeuwse premonstratenzer kerken, 1999)
Besteladres: Herman Janssens, Abdijstraat 1, B-3271 Averbode (B)

Mirakels historisch. De exempels van Caesarius van Heisterbach over Nederland en de Nederlanders - Moolenbroek, J.J. van (Middeleeuwse studies en bronnen, 1999)

Moines et chanoines du pays mosan et du conflent au XIe siècle. Contribution à l'étude des mentalités médiévales - Stiennon, Jacques (Un Moyen Âge pluriel. Recueil d'articles, 1999)

Manuscriptproductie en randversieringen in Noord-Brabant - Beer, Richard W.M. de (Cultuur in het laatmiddeleeuwse Noord-Brabant. Literatuur - boekproductie - historiografie, 1998)

Meester Paschase de Zouter, monitor te Gent (1518), schoolrector te Ieper (1524) en pastoor van de Sint-Jansparochie te Poperinge (1528) - Schoonaert, Germain (Westhoek, 1998)

Mission bis Millenium. 313-1000 - Angenendt, Arnold (Geschichte des Bistums Münster, 1998)

Monasticon van Zwartzusters-Augustinessen in België - Vanden Bosch, Gerrit (Bibliografische inleiding tot de Belgische kloostergeschiedenis vóór 1796, 1998)

Middeleeuws grootgrondbezit van het Maastrichtse Sint-Servaaskapittel in Vlijtingen - Hackeng, Rolf A.W.J. (Publications de la Société Historique et Archéologique dans le Limbourg, 1997)

Middeleeuwse witte en zwarte magie in het Nederlands taalgebied. Gecommentarieerd compendium van incantamenta tot einde 16de eeuw - Braekman, Willy L. (Koninklijke academie voor Nederlandse taal- en letterkunde. 6de reeks, Bekroonde werken, 1997)

Miles en monachus. De fundamentele constellatie van de geestelijke ridderorden in de Middeleeuwen - Fleckenstein, Josef (Crux et arma. Kruistochten, ridderorden en Duitse Orde, 1997)

Minderbroederkloosters in de Zuidelijke Nederlanden. 62. Sint-Truiden (1230) - Ceyssens, Lucien (Franciscana, 1997)

Muziek in de Brugse Onze-Lieve-Vrouwekerk, 1291-1583 - Dewitte, Alfons (Sacris Erudiri, 1997)

Muziek in de handschriften van de Sint-Pieters- en Sint-Baafsabdij - Haggh, Barbara (Ganda et Blandinium. De Gentse abdijen van Sint-Pieters en Sint-Baafs, 1997)

Maria ter Nood Gods - Goudriaan, Koen (Tidinge van die Goude. Mededelingenblad Oudheidkundige Kring "Die Goude", 1996)

Menno Simons als pastoor - Mol, J.A.(Hans) (Doopsgezinde Bijdragen, 1996)

Meum summum desiderium est te habere. De Eucharistie als sacrament van de godsontmoeting voor alle gelovigen, ca. 1200 - ca. 1500 - Caspers, Charles M.A. (Ons Geestelijk Erf, 1996)

Middeleeuwse bezitsverhoudingen in Noordoost-Fivelgo - Noomen, Paul N. (Het Bierumer boerderijenboek. Een bijdrage tot de geschiedenis van Noordoost-Fivelgo, 1996)
Hierin veel informatie over de ontwikkeling van het parochiewezen en de goederenexploitatie van de kloosters Feldwerd (benedictijnen) en Nijeklooster of Rozenkamp (premonstratenzers)

Middeleeuwse vrome schenkingen als instrument van sociale integratie en politieke machtsvorming. Een historiografisch overzicht - Bijsterveld, A.J.A. (Tijdschrift voor Geschiedenis, 1996)

Missionaries, Masters and Manuscripts; a survey of the oldest books and their patrons in the diocese of Utrecht (until c. 1200) - Wüstefeld, Wilhelmina C. M. (Utrecht: Britain and the continent. Archaeology, art and architecture, 1996)

Magie in het oude hertogdom Brabant. Een onderzoek naar de heksenwaan en de waan der historici - Gielis, Marcel (De Betovering van het middeleeuwse christendom. Studies over ritueel en magie in de Middeleeuwen, 1995)

Mandatory celibacy and priestly ministry in the diocese of Tournai at the end of the Middle Ages - Vleeschouwers-Van Melkebeek, Monique (Peasants and Townsmen in Medieval Europe. Studia in honorem Adriaan Verhulst, 1995)

Middeleeuwse ‘Membra Disjecta’ in het Rijksarchief in Overijssel te Zwolle - Wüstefeld, E.M.F. (Overijsselse historische bijdragen, 1995)

Minderbroederkloosters in de Zuidelijke Nederlanden. 57. Mons/Bergen (1228-1797) - Ceyssens, Lucien (Franciscana, 1995)

Misgezangen voor het hoogfeest van St Willibrord - Rijkers, Henk (Willibrord tussen Ierland en Rome. Een bundel historische en muzikaal-liturgische bijdragen, 1995)

Monastic collectaria from the abbey of St. Trudo (Limburg) and the reception of writings by Denys the Carthusian - Emery Jr, Kent (Literature and Religion in the Later Middle Ages. Philological Studies in Honor of Siegfried Wenzel, 1995)

Mesen. Een kleine stad met een grote geschiedenis - Beijn, J. (Tijdschrift van het gemeentekrediet, 1994)
Een artikel met aandacht voor de stadsontwikkeling van het Vlaamse stadje Mesen en de rol daarin van de O.l.V.-abdij (benedictinessen)

Middeleeuwse stegen in de stadsgeschiedenis: de Coppe-Lanensteeg - Melker, Bas R. de (Maandblad Amstelodanum, 1994)
Over een Amsterdamse steeg die zijn naam dankte aan de stichter van het Amsterdamse begijnhof, met enkele bijzonderheden over deze Coppe (van der) Laen en zijn familie

Minderbroederkloosters in de zuidelijke Nederlanden. 56. Tournai/Doornik (1230-1798) - Ceyssens, Lucien (Franciscana, 1994)

Martyrologes manuscrits des anciens diocèses d'Utrecht et de Liège. Etude sur le développement et la diffusion du martyrologe d'Usuard - Overgaauw, Eef A. (Middeleeuwse studies en bronnen, 1993)

Minderbroederkloosters in de Zuidelijke Nederlanden. 53. Tienen (1226-1797) - Ceyssens, Lucien (Franciscana, 1993)

Monnikenwerk? Egmond en de dijkzorg in Noord-Holland - Zeiler, Frits David (Egmond tussen Kerk en wereld, 1993)

Middeleeuwse tegelvloeren in confrontatie met schilderijen van de Vlaamse primitieven en miniaturen: tevens catalogus van de tegels en vloeren tentoongesteld in de Boudelozaal van het Stedelijk Museum te Sint-Niklaas - De Belie, Alfons (Uitgave van de Culturele Kring Boudelo, 1992)

Macht en onderhorigheid binnen de Ridderlijke Orde van Sint Jan. De commandeursportretten uit het Sint Jansklooster te Haarlem - Bueren, Truus van (Schuyt, 1991)

Minderbroederkloosters in de Zuidelijke Nederlanden. Nivelles (Nijvel) - Ceyssens, Lucien (Franciscana, 1991)

Moines et nature sauvage dans l'Ardenne du haut Moyen Âge: saint Remacle à Cugnon et à Stavelot-Malmédy - Noël, René (Villes et campagnes au Moyen Âge. Mélanges Georges Despy, 1991)